O Brasil e a medicina tropical Brazil and tropical medicine - Oswaldo Paulo Forattini (Universidade de São Paulo, 1997)
São feitas considerações sobre o papel das endemias tropicais no desenvolvimento da sociedade brasileira. Aborda-se a atualidade das pesquisas que tratam da temática das doenças infecciosas. Comparando o significado para o primeiro mundo, conclui-se pela necessidade de estimular as pequisas nessa área e de prestigiar os periódicos nacionais destinados a divulgá-las. Endemic infectious diseases still constitute a threat to Latin American countries. In view of this, research on tropical medicine should be encouraged, particularly in countries like Brazil where this kind of scientific investigacion was historically highly early in this century. It is suggested that more resources should be made available to stimulate such studies and the publication in English, Portuguese and Spanish.